Multidrug resistance and ESBL-producing Salmonella spp. isolated from broiler processing plants - Ziech, Rosangela Estel; Lampugnani, Camila; Perin, Ana Paula; Sereno, Mallu Jagnow; Sfaciotte, Ricardo Antônio Pilegi; Viana, Cibeli; Soares, Vanessa Mendonça [UNESP]; de Almeida Nogueira Pinto, José Paes [UNESP]; dos Santos Bersot, Luciano (Springer Nature, 2016)
The aim of this study was to investigate the occurrence of multidrug-resistant, extended spectrum beta-lactamase (ESBL) producing Salmonella spp. isolated from conveyor belts of broiler cutting rooms in Brazilian broiler processing plants. Ninety-eight strains of Salmonella spp. were analyzed. Multidrug resistance was determined by the disk diffusion test and the susceptibility of the isolated bacteria was evaluated against 18 antimicrobials from seven different classes. The double disk diffusion test was used to evaluate ESBL production. Of the 98 strains tested, 84 were multidrug resistant. The highest rates of resistance were against nalidixic acid (95%), tetracycline (91%), and the beta-lactams: ampicillin and cefachlor (45%), followed by streptomycin and gentamicin with 19% and 15% of strain resistance, respectively. By contrast, 97% of the strains were sensitive to chloramphenicol. 45%of the strains were positive for the presence of ESBL activity. In this study, high rates of multidrug resistance and ESBL production were observed in Salmonella spp.
Keywords: Antimicrobial resistance; Food borne pathogens; Salmonella spp